Measurement of forward top pair production in the dilepton channel in pp collisions at √s = 13 TeV - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Esen, Sevda; Gerick, David; Grünberg, Oliver; Han, Xiaoxue; et al. (Journal of high energy physics, 2018)
Forward top quark pair production is studied in pp collisions in the μeb final state using a data sample corresponding to an integrated luminosity of 1.93 fb−1 collected with the LHCb experiment at a centre-of-mass energy of 13 TeV. The cross-section is measured in a fiducial region where both leptons have a transverse momentum greater than 20 GeV and a pseudorapidity between 2.0 and 4.5. The quadrature sum of the azimuthal separation and the difference in pseudorapidities, denoted ΔR, between the two leptons must be larger than 0.1. The b-jet axis is required to be separated from both leptons by a ΔR of 0.5, and to have a transverse momentum in excess of 20 GeV and a pseudorapidity between 2.2 and 4.2. The cross-section is measured to beσtt¯=126±19stat±16syst±5lumifb$$ σ_{t\overline{t}}=126± 19\left(stat\right)± 16\left(syst\right)± 5\left(lumi\right)fb $$where the first uncertainty is statistical, the second is systematic, and the third is due to the luminosity determination. The measurement is compatible with the Standard Model prediction.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, M. De Cian, M. Dziewiecki, S. Esen, D. Gerick, X. Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, R. Kopecná, B. Leverington, J. Marks, D. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und 769 weitere]
Gesehen am 30.06.2020